Salmonella Modulates B Cell Biology to Evade CD8+ T Cell-Mediated Immune Responses - Lopez-Medina, Marcela; Perez-Lopez, Araceli; Alpuche-Aranda, Celia; Ortiz-Navarrete, Vianney (Frontiers in Immunology, 2014)
Although B cells and antibodies are the central effectors of humoral immunity, B cells can also produce and secrete cytokines and present antigen to helper T cells. The uptake of antigen is mainly mediated by endocytosis; thus, antigens are often presented by MHC-II molecules. However, it is unclear if B cells can present these same antigens via MHC-I molecules. Recently, Salmonella bacteria were found to infect B cells, allowing possible antigen cross-processing that could generate bacterial peptides for antigen presentation via MHC-I molecules. Here, we will discuss available knowledge regarding Salmonella antigen presentation by infected B cell MHC-I molecules and subsequent inhibitory effects on CD8+ T cells for bacterial evasion of cell-mediated immunity.